Asset ownership and incentives in early shareholder capitalism: Liverpool shipping in the eighteenth century1. (7th July 2016) - Silverman, Brian S.; Ingram, Paul
Abstract : Research summary : We explore captain‐ownership and vessel performance in eighteenth‐century transatlantic shipping. Although contingent compensation often aligned incentives between captains and shipowners, one difficult‐to‐contract hazard was threat of capture during wartime. We exploit variation across time and routes to study the relationship between capture threat and captain‐ownership. Vessels were more likely to have captain‐owners when undertaking wartime voyages on routes susceptible to privateers. Captain‐owned vessels were less readily captured than those with nonowner captains, but more likely to forgo voyage profits to preserve the vessel's safety. These results are consistent with multitask agency, where residual claims to asset value rather than control rights influence captain behavior. This article is among the first to empirically isolate mechanisms distinguishing among major strands of organizational economics regarding asset ownership and performance . Managerial summary : Organizations face an enduring challenge: Owners hire an executive to act on their behalf, but it is difficult to ensure that the executive indeed acts in their interests. In this study, we exploit a useful historical context—eighteenth‐century transatlantic shipping from Liverpool—to explore the cause and effect of a captain's becoming part‐owner of his vessel. Captains became part‐owners for voyages likely to encounter enemy privateers. Captain‐owners were less likely to be captured, but were more willing to forgo cargo profits to preserve the vessel's safety. Our results provide a useful analogy to modern firm owners who must determine whether to award equity to executives, and to managers who must determine whether to provide assets to employees or rely on employee self‐provision of assets (e.g., tools for tradespeople) . Copyright © 2016 John Wiley & Sons, Ltd.